2014
DOI: 10.1007/s10566-014-9275-9
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Anxiety Symptoms and Identity Processes in Cross-Cultural Samples of Adolescents from the General Population

Abstract: Background Approximately 20 % of adolescents around the world experience mental health problems, most commonly depression or anxiety. High levels of anxiety disorder symptoms can hinder adolescent development, persist into adulthood, and predict negative mental outcomes, such as suicidal ideation and attempts. Objectives We analyzed generalized anxiety disorder (GAD) symptoms in cross-cultural samples from the general population. We sought to examine cultural and gender differences, and correlates of GAD sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 60 publications
1
15
1
3
Order By: Relevance
“…In recent years, several cross-cultural studies were conducted on the associations between identity processes and mental health (Crocetti et al, 2015), well-being (Karaś, Cieciuch, Negru, & Crocetti, 2015), life satisfaction (Dimitrova et al, 2018), and parental trust and emotional separation (Sugimura et al, 2018). These studies focus mostly on adolescents in diverse cultural settings.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several cross-cultural studies were conducted on the associations between identity processes and mental health (Crocetti et al, 2015), well-being (Karaś, Cieciuch, Negru, & Crocetti, 2015), life satisfaction (Dimitrova et al, 2018), and parental trust and emotional separation (Sugimura et al, 2018). These studies focus mostly on adolescents in diverse cultural settings.…”
Section: The Present Studymentioning
confidence: 99%
“…Several studies reported an association between internalizing disorders, especially depression, and ruminative exploration (Kroger, 2007; Luyckx, Seiffge-Krenke, et al, 2008; Seiffge-Krenke & Escher, 2018). Generalized anxiety symptoms were also related to identity processes (Crocetti et al, 2015). Links to externalizing disorders were less frequently found (Crocetti, Klimstra, Hale, Koot, & Meeus, 2013).…”
Section: Identity Development: Oscillating Between Adaptation and Psymentioning
confidence: 99%
“…Indeed, understanding the role of cultural context in identity development (Baumeister & Muraven, 1996) requires that diverse cultural contexts be studied. With increasing globalization, research conducted with identity status models has begun to expand beyond the West (Crocetti et al, 2015; Morsünbül, Crocetti, Çok, & Meeus, 2014). The present study represents another step in this direction.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, identity researchers took up the challenge of studying more in‐depth the “neglected 95%” (Arnett, 2008), largely increasing the number of studies in non‐American samples. These studies include both studies focusing on identity in specific understudied national groups (e.g., identity in Filipino youth; Pesigan, Luyckx, & Alampay, 2014) as well as cross‐cultural comparisons involving youth from different continents (Crocetti et al, 2015). This increase in diversity is highlighting international perspectives in similarities and differences in how youth around the globe develop their identity (Berman, 2011; Schwartz, Zamboanga, Meca, & Ritchie, 2012).…”
Section: Identity Literature: a Look At Recent Developments Of The Fieldmentioning
confidence: 99%